Voltammetric study and electrochemical degradation of reactive dyes - Esteves, M. de Fátima (2005)
The aim of this study was, in a first stage, to investigate the voltammetric behavior of two reactive dyes, C.I.Reactive Orange 16 and C.I.Reactive Blue 19. Cyclic voltammetry technique (CV), on a glassy carbon electrode, was used for this purpose in order to identify the electrochemical activity of the chromophore group in each case, in the present experimental conditions. A second part of the study was to investigate the electrochemical degradation of the dyes, in the presence of hydrogen peroxide and copper ions. The reaction between the two species leads to the generation of hydroxyl radicals, which causes the oxidation and degradation of the organic compounds. The efficiency of dye degradation and ecolorization were evaluated by color removal and COD values. Depending on electrolysis time, applied potential, hydrogen peroxide concentration and dye concentration, different stages of color removal were attained.